2012
DOI: 10.1039/c2sm25519g
|View full text |Cite
|
Sign up to set email alerts
|

Lipid membrane deformation in response to a local pH modification: theory and experiments

Abstract: We study the deformation of a lipid membrane in response to a local pH modification. Experimentally, a basic solution is microinjected close to a giant unilamellar vesicle. A local deformation appears in the zone of the membrane that is closest to the micropipette, and relaxes when the injection is stopped. A theoretical description of this phenomenon is provided. It fully takes into account the spatiotemporal evolution of the concentration of hydroxide ions during and after the microinjection, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 25 publications
1
66
0
Order By: Relevance
“…For example, the pH values of the solvents are known to affect the lipid membrane stability. 24 We are now investigating how the electrohydrodynamic instability reported in this work might be affected by the pH values of solvents.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the pH values of the solvents are known to affect the lipid membrane stability. 24 We are now investigating how the electrohydrodynamic instability reported in this work might be affected by the pH values of solvents.…”
Section: Discussionmentioning
confidence: 97%
“…This is responsible for the pseudopod-like extrusion toward the higher-pH side. 20 To confirm the effect of the pH gradient, we used HCl as the diffusing species. The pseudopod-like structures were extruded toward the side of the vesicle surrounded by the higher pH in this experiment as well (see SI Figure S4-1).…”
Section: Resultsmentioning
confidence: 99%
“…Standard parameter values are eC 1 nm, k C 0:1 J/m 2 , κ C 10 À 19 J, bC10 9 J s/m 4 , η s C10 À 9 J s/m 2 and η C 10 À 3 J s/m 3 [17][18][19][20]11]. It follows that the relaxation time τ ¼ 2ðη=q þ η s Þ=k in (60) is extremely short, e.g., of order τ C 10 ns for π=q C 1 μ m. This is because the average density ρ relaxes without causing any intermonolayer friction.…”
Section: Dynamical Equations For the Membrane In Fourier Spacementioning
confidence: 99%
“…In the early studies of membrane hydrodynamics the bilayer structure of the membrane was neglected [5,6]. While this is a good approximations for tensionless membranes at length-scales much larger than microns, experiments and theoretical studies have shown that taking into account the bilayer structure is essential at lower length-scales [7][8][9][10][11]. This is chiefly due to the importance of the dissipation caused by intermonolayer friction.…”
Section: Introductionmentioning
confidence: 97%